(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
Investments in shares represent an essential component of companies’ assets and a source of profit making resources. These investments are linked to the areas of trading and speculation, which is reflected on their market value, which makes accounting for and evaluating these investments require their own accounting standards, and thus several international standards were issued regarding this as well as a statement of their impact on growth Sustainable, as the research problem is to show the impact of measuring investments in shares according to international accounting and financial reporting standards on the sustainable growth of economic units, the research sample and its reflection on audit procedures. In accordance with international accounting and financial reporting standards, as well as measuring and analyzing the sustainable growth rate by identifying the concept of sustainable growth and ways to measure it. The research concluded with a set of conclusions, the most important of which is that the adoption of international standards for companies for the first time clearly reflected on the value of investment in shares compared to the local rules, as differences appeared in the balance of investments according to the principle of cost over the balance after the application of international standard (9) which represents the minimum to guide the external auditor in conducting the audit process. Accurate, which leads to the provision of more accurate information to the users of this information.